Isotopic Composition of Lead in Copper Ores and a Copper Artefact from the La Profunda Mine (León, Spain). (28th May 2013) - Huelga‐Suarez, G.; Moldovan, M.; Suárez Fernández, M.; de Blas Cortina, M. Ángel; García Alonso, J. I.
<x xml:space="preserve">Abstract</x> This paper continues the characterization of the lead isotopic fingerprint of ancient copper mines in the north‐west of Spain. In this work, the lead isotopic compositions found in copper ores from the La Profunda mine are presented. Azurites and malachites sampled from this deposit were subjected to lead isotope analysis by multicollector ICP–MS. The results showed a clear radiogenic lead signature compatible with the presence of uranium‐rich minerals (such as zeunerite) in the same mining complex. Moreover, a rare copper artefact, found in the galleries of the mine during its modern exploitation, was also analysed and showed that local mineral was used for its manufacturing.